Conventions and practical interpretation in Westminster-type constitutional systems. (6th February 2023) - Harding, Andrew
Abstract: This article focuses on what are termed "practical interpretations"—that is, constitutional interpretations given by the executive or legislative branch. It does so principally in relation to constitutional conventions in Westminster-type systems, which are normally not subject to judicial review. The argument is that these practical interpretations are of great significance, and more attention needs to be paid to them and to understanding how they are made, as they are at least equally important as judicial interpretations, in spite of expanding judicial review of conventions. In order to establish how nonjudicial interpretation operates, the discussion goes beyond the United Kingdom to consider how certain conventions, when transplanted elsewhere, receive very different interpretations. In the course of making this argument, the article explores the constitutional importance of practical interpretation, examining in the process the extent of judicial review of conventions.